The one-way street of integration : fair housing and the pursuit of racial justice in American cities - Goetz, Edward G. (Edward Glenn), 1957- (Cornell University Press, 2018)
The One-Way Street of Integration examines two contrasting housing policy approaches to achieving racial justice. Integration initiatives and community development efforts have been for decades contrasting means of achieving racial equity through ...